Особенности формирования политического стиля мышления в современном обществе - Гаряева, Анна Михайловна; Муренко, Елена Леонидовна (SRL "Tipocart Print", Chişinău, 2018)
Проблема формирования постметафизического стиля мышления является одной из центральных в современной философии, оказывая существенное влияние на развитие общего стиля теоретизирования в социально-гуманитарных науках. Ее исследование важно для осознания особенностей концептуального базиса современного философского мировоззрения и оснований науки. Интерес к ней обусловлен тем, что вопросы, вызванные к жизни изменениями в теоретической мысли, находят отражение в культуре, практике и политической жизни современного общества.

The problem of forming a post-metaphysical style of thinking is one of the central in modern philosophy, exerting a significant inflence on the development of a general style of theorizing in the social and human sciences. Her research is important for understanding the features of the conceptual basis of the modern philosophical worldview and the foundations of science. Interest in it is due to the fact that the issues brought to life by changes in theoretical thought are reflected in the culture, practice and political life of modern society
Features of formation of political style of thinking in modern society
Keywords: интеллектуальные технологии; постметафизическая философия; постмодернизм; интеллект; intellectual technologies; post-metaphysical philosophy; postmodernism; intellect